Propiedades Mecánicas, Térmicas y Físicas de bandejas hechas de Almidón de Oca (oxalis tuberosa) incorporando Fibra de Residuos Agroindustriales - Beltran Ramos, Patricia Elizabeth (2017)
Sugarcane bagasse and asparagus peel, agroindustrial residues, were used to produce biodegradable foam trays made from goose starch using a cooking process. These foams were made with different fiber concentrations (0% - 40%, w / w) and were characterized according to their microstructure, physical, thermal and mechanical properties. The addition of fibers to the oca starch produced a yellowish tray with less luminosity and greater porosity, mechanical strength, deformability and water absorption capacity compared to the fiber reduce oca-starch foam tray. Low fiber concentrations reduce the density of the foams and the addition of fiber does not improve the flexural strength of the trays, but generates harder and deformable trays. The high concentrations of sugarcane bagasse fiber generate more compact trays with a lower water absorption capacity than the control. The trays with asparagus pearl fiber showed higher rates of thermal degradation than the control but not so extensive as to affect its applicability